Risk of occupational radiation-induced cataract in medical workers / Rischio di cataratta indotta da radiazioni in operatori della sanità - Milacic, S. (La Medicina del Lavoro, 2009)
Background: Ionizing radiation  on the lens of the eye can produce a progressive cataract. Small cumulative doses, over a long time period, can produce adverse effects on the professional capabilities of health workers in the ionizing radiation zone. Objectives: The aim of this study was to ascertain whether occupational exposure to low levels of ionizing radiation can cause an increase in prevalence of cataract. Method: We compared a group with occupational cataract, consisting of 115 health workers in the ionizing radiation zone, and two control groups: a group of 100 health-care workers in the ionizing radiation zone, with a higher incidence of chromosomal aberrations, but without cataract; and another control group of 26 health-care workers with cataract, outside the zone; all risk factors for the development of cataract were considered: age, sex, difference in profession, duration of occupational exposure, years of service, level of blood sugar, blood pressure, arrhythmias, etc. Results: A more significant incidence of cataract was found in workers in the ionizing radiation zone, where the relative risk was 4.6; p